The role of the tumor microenvironment in HNSCC resistance and targeted therapy - Guo, Zhaomeng; Li, Kang; Ren, Xiaotong; Wang, Xijia; Yang, Dunhui; Ma, Shibo; Zeng, Xianhai; Zhang, Peng (Frontiers in Immunology, 2025)
The prognosis for head and neck squamous cell carcinoma (HNSCC) remains unfavorable, primarily due to significant therapeutic resistance and the absence effective interventions. A major obstacle in cancer treatment is the persistent resistance of cancer cells to a variety of therapeutic modalities. The tumor microenvironment (TME) which includes encompasses all non-malignant components and their metabolites within the tumor tissue, plays a crucial role in this context. The distinct characteristics of the HNSCC TME facilitate tumor growth, invasion, metastasis, and resistance to treatment. This review provides a comprehensive overview of the HNSCC TME components, with a particular focus on tumor-associated macrophages (TAMs), regulatory T cells (Tregs), myeloid-derived suppressor cells (MDSCs), cancer-associated fibroblasts (CAFs), the extracellular matrix, reprogrammed metabolic processes, and metabolic products. It elucidates their contributions to modulating resistance to chemotherapy, radiotherapy, targeted therapy, and immunotherapy in HNSCC, and explores novel therapeutic strategies targeting the TME for HNSCC management.